2021
DOI: 10.3389/fonc.2021.805459
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Microbiota and Prostate Cancer: A New Trend in Treatment

Abstract: Although the incidence and mortality of prostate cancer have gradually begun to decline in the past few years, it is still one of the leading causes of death from malignant tumors in the world. The occurrence and development of prostate cancer are affected by race, family history, microenvironment, and other factors. In recent decades, more and more studies have confirmed that prostate microflora in the tumor microenvironment may play an important role in the occurrence, development, and prognosis of prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 168 publications
(173 reference statements)
0
22
0
Order By: Relevance
“…Previous studies investigated the differences between the gut microbiota of prostate cancer patients and healthy individuals. Che et al found a higher relative abundance of Bacteroides massiliensis and a lower relative abundance of Faecalibacterium prausnitzii in prostate cancer patients’ gut microbiota [ 31 ]. Golombos et al 2018 found a higher relative abundance of Bacteroides massiliensis and a lower relative abundance of Feacalibactereium prausnitzii and Eubacterium rectale [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated the differences between the gut microbiota of prostate cancer patients and healthy individuals. Che et al found a higher relative abundance of Bacteroides massiliensis and a lower relative abundance of Faecalibacterium prausnitzii in prostate cancer patients’ gut microbiota [ 31 ]. Golombos et al 2018 found a higher relative abundance of Bacteroides massiliensis and a lower relative abundance of Feacalibactereium prausnitzii and Eubacterium rectale [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…CP1 also increases T-cell toxicity and immune death of tumor cells, and CP1 increases infiltration of activated CD8 T cells, Th17 T cells, mature dendritic cells, M1 macrophages, and NK cells into tumors, and intraurethral administration of CP1 specifically enters and colonizes the tumor without causing any systemic toxicity (46). There have also been many studies using microbes as targets for PCA (47)(48)(49).…”
Section: Prostate Cancermentioning
confidence: 99%
“…Over the last few years, increasing attention has been paid to the host gut microbiome defined as the collection of genomes from all microorganisms in the gastrointestinal tract, especially within the intestines. However, it has been demonstrated that the microbiome in general (not only the gut, but also local or even intratumoral microbiome) is associated with the pathogenesis of various cancers such as colorectal, breast, ovarian, lung, and prostate cancers [ 66 , 67 , 68 , 69 , 70 ]. For example, compared to a healthy population, the fecal gut microbiome in CRC patients is enriched with Prevotella , Collinsella , and Peptostreptococcus and contained significantly lower concentrations of Escherichia-Shigella [ 70 ].…”
Section: Metronomic Chemotherapy—mechanisms Of Actionmentioning
confidence: 99%